Influence of Different Stabilizers on Dissolution of Cilnidipine Nanosuspension - Subramanian, Dr. S. (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: Cilnidipine is a new antihypertensive agent and it is categorized under the biopharmaceutical Class-II drug. Hence, our perspective is to improve dissolution through in vitro rate of Cilnidipine. Materials and Methods: Nanosuspensions are a good choice for enhancing the solubility of poorly water-soluble drugs and improve bioavailability. Cilnidipine nanosuspension was formulated by pure drug with poloxamer-188, polyvinylpyrrolidone K-30 as stabilizer, polyethylene glycol-4000 as polymer, and ethanol as solvent. Nanosuspension technique such as combination technique of antisolvent precipitation and high-speed homogenization is involved in the formulation. Results and Discussion: Cilnidipine nanosuspension is characterized by particle size, polydispersity index, zeta potential, atomic force microscopy, and scanning electron microscopy. Cilnidipine nanosuspension converted into powder by lyophilization process and 1% mannitol was used as lyoprotectant. Lyophilized powder was analyzed for drug content at 240 nm by ultraviolet spectroscopy. After that, lyophilized powder was formulated to tablet. Formulated tablet was analyzed for weight variation, disintegration, friability, hardness, thickness, and in vitro drug release. In vitro drug release was studied by distinguishing between formulated and marketed tablet. Conclusion: Cilnidipine nanoformulation was proved with 18.59% increase in in vitro release when compared to Cilnidipine marketed tablets.